Effect of preoperative radiotherapy on the prognosis of patients with stage cTxN0M0 esophageal squamous cell carcinoma: propensity score matching analysis based on SEER database - Jin, Zixian; Sun, Jiajing; Zhang, Jian; Shen, Jianfei; Zhang, Bo (Frontiers in Surgery, 2023)
Objective: The aim of this study was to investigate the effect of preoperative radiotherapy (RT) on overall survival (OS) in patients with stage cTxN0M0 esophageal squamous cell carcinoma (ESCC). Methods: A total of 467 patients with ESCC diagnosed as cTxN0M0 and undergoing esophagectomy between 2004 and 2016 were downloaded from the Surveillance, Epidemiology, and End Results (SEER) database. According to the presence or absence of preoperative RT, the patients were divided into preoperative RT group and non-preoperative RT group. Propensity score matching (PSM) was performed to equalize baseline levels between groups. Univariate and multivariate Cox regression analyses were used to compare the survival differences between the two groups. Results: Using PSM, 162 pairs of patients were selected. Preoperative RT was not a prognostic factor for OS in all patients with cTx stage. After PSM, for patients with cT1-2 stage, univariate Cox regression analysis showed that preoperative RT was an influencing factor of OS, and multivariate Cox regression analysis confirmed that preoperative RT was an independent predictor of OS. Compared with non-preoperative RT, preoperative RT significantly decreased OS (HR=1.556, 95%CI 1.008-2.464, P=0.046). For patients with cT3-4, univariate Cox regression analysis showed that preoperative RT was an influencing factor for OS, and multivariate Cox regression analysis determined that preoperative RT was independent predictors of survival. Compared with non-preoperative RT, preoperative RT significantly improved the OS (HR=0.479, 95%CI 0.272-0.841, P=0.010). Conclusion: For ESCC, preoperative RT can improve the OS of patients with cT3-4N0M0. However, preoperative RT is not suitable for patients with cT1-2N0M0.